Legality of Bitcoin in Business Transactions in Indonesia - Ilyasa, Raden Muhammad Arvy (Universitas Negeri Semarang, 2019)
The world is currently facing the phenomenon of disruption, where the movement of the industrial world is moving very quickly from the old order to the new order. Developments in the economic field in this era are in line with technological developments, and one of the developments in the economic field is the emergence of Bitcoin. Bitcoin is a virtual money that uses Cryptocurrency technology, as one of the famous virtual money is becoming a new trend as an international payment with all the benefits. Among the existing Cryptocurrencies that stand out the most is Bitcoin. In Indonesia, Bitcoin has attracted attention because of its several advantages and has started to carry out major expansions and has a separate marketplace available. In circulation in Indonesia, Bitcoin has become a polemic in itself in the world and in Indonesia. There are several countries in the world that legalize Bitcoin circulation and have legal regulations and there are also countries that strictly prohibit its circulation. In Indonesia itself there is no clarity whether Bitcoin may be used or not as a currency, as well as the attitude of the government which states that all risks of using Bitcoin are borne by the owner and use of Bitcoin in Indonesia which is contrary to article 28 of the 1945 Constitution which states that the state must guarantee certainty law and legal protection for every citizen.